DATA ANALYTICS UNTUK AKUNTANSI MANAJEMEN DALAM SUPPLY CHAIN MANAGEMENT – A SYSTEMATIC LITERATURE REVIEW - Mutiara Aisya Kamila; Totok Dewayanto (Diponegoro Journal of Accounting, 2026)
Management accounting practices and the use of Information Technology have changed significantly over the years, especially for those working in Supply Chain Management (SCM). Data analytics is now part of the decision-making process, the controlling of costs, and measuring performance. This research systematically examines the existing literature on the effect of data analytics on management accounting within SCMs, following the PRISMA Protocol and including articles published in the Scopus databases from 2022 through 2025. The systematic review indicates the manner in which data analytics aids in planning, controlling costs, and measuring performance, but also outlines critical success factors, as well as the challenges encountered while implementing data analytics. Further, the Resource-Based View of Data Analytics is presented as an Organizational Capability, which creates a means for improving the effectiveness of Management Accounting by providing valuable firm-specific insights that cannot be easily replicated, particularly when paired with Managerial Expertise, Internal Processes and Decision-Routines across SCMs. Findings are discussed in the context of Contingency Theory, which highlights the need to ensure that technology, organizational structure and the business environment are aligned. The information provided from this systematic review can aid in the creating of digital management accounting, by giving an organization a map of how to implement data analytics against SCM decision making activities.